PALATAL MEMORY PLATE IN TRISSOMY 21: BENEFITS OF EARLY INTERVENTION IN OROFACIAL DEVELOPMENT - Dalapicola, Kely; Vendel, Ana Lúcia (Seven Editora, 2026)
The Palatal Memory Plate (PMP) is a transdisciplinary therapeutic resource aimed at early intervention in infants with Trisomy 21 (T21) and in cases of marked orofacial hypotonia. Indicated from two months of age, the PMP promotes the balance of the stomatognathic system, favoring vital functions such as nasal breathing, sucking, swallowing, chewing, and phonation, positively impacting the individual’s overall development. Children with T21 frequently present orofacial characteristics such as hypoplasia of the midface, relative pseudomacroglossia, delayed tooth eruption, malocclusions, and labial and lingual hypotonia, which can compromise breastfeeding, swallowing, breathing, and sleep. Early intervention with PPM (Positive Myofunctional Therapy), combined with myofunctional therapy, acts on the postural reorganization of the tongue and lips, stimulates lip seal, automates nasal breathing, and strengthens the orofacial musculature, promoting harmonious development of the face and stomatognathic functions. Ten infants with Down syndrome (T21) were evaluated, and this study demonstrates that the application of PPM, accompanied by speech therapy and pediatric dentistry guidance, resulted in significant improvement in the habitual posture of the tongue and lips, muscle adaptation, and feeding functions. The effectiveness of PPM depends on adequate supervision and multidisciplinary integration, representing an effective therapy when the intervention is early, contributing to the reorganization of the orofacial musculature, prevention of future alterations and malocclusions, and improvement in the quality of life of people with T21.